2009
DOI: 10.1016/j.carbon.2009.03.052
|View full text |Cite
|
Sign up to set email alerts
|

The use of graphite oxide to produce mesoporous carbon supporting Pt, Ru, or Pd nanoparticles

Abstract: Mesoporous carbon having platinum, ruthenium or palladium nanoparticles on exfoliated graphene sheets were produced from graphite oxide (GO) and metal complexes. The Pt included carbon was made by heating of the intercalation compound including tetraammineplatinum (II) chloride monohydrate. Samples having Ru or Pd are producible by heating in nitrogen gas atmosphere using hexaammineruthenium (III) chloride or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Gotoh et al [220,221] also proved that Pd supported on graphene oxide showed better performance in ORR than Pt.…”
Section: Pd Supported On Graphenementioning
confidence: 99%
“…Gotoh et al [220,221] also proved that Pd supported on graphene oxide showed better performance in ORR than Pt.…”
Section: Pd Supported On Graphenementioning
confidence: 99%
“…Those catalysts were active, however no comparison with other systems was made and the metal loading was higher than that employed in the present work, i.e. 10-25 wt.% [45][46]. Alternatively, the impregnation could have been performed before the reduction of GO but, in that case, the inert surface may also lead to low dispersion.…”
Section: Reactionmentioning
confidence: 88%
“…Heterogeneous surfaces are reported to better stabilise the metal in a highly dispersed state. It has been reported that Pd/GRO shows a better ORR activity and forms a four-electron oxygen-reduction process compared to Pt [87][88][89]. N-doped graphene has been reported to show an improved electrocatalytic activity towards ORR compared to graphene in acidic and alkaline media [90].…”
Section: Electrocatalysts For Fuel Cells and Hydrogen Evolution -Theomentioning
confidence: 99%